An abrupt oceanic change and frequent climate fluctuations across the Frasnian–Famennian transition of Late Devonian: Constraints from conodont Sr isotope. (21st November 2019) - Zhang, Liyu; Chen, Daizhao; Huang, Taiyu; Yu, Hao; Zhou, Xiqiang; Wang, Jianguo
Abstract : The Late Devonian Frasnian–Famennian (F‐F) transition witnessed one of the "big five" mass extinction events in the Phanerozoic. We here present high‐resolution conodont Sr isotopic data from Fuhe (South China) and Kowala (South Central Poland) sections to reveal coeval climatic and environmental variations and potential causes of this biotic crisis. Fuhe and Kowala sections yield 87 Sr/ 86 Sr ratios from 0.70815 to 0.70864 and 0.70808 to 0.70836, respectively. These Sr isotopic data demonstrate three distinctive variation cycles (I, II, and III), notably at Fuhe, fluctuating from low (negative) to higher Sr isotope ratios (positive excursion). Temporally, fluctuations I and II occurred immediately before the F‐F boundary, and fluctuation III started almost from the onset of the Famennian age. These conodont 87 Sr/ 86 Sr (low‐to‐high) fluctuations temporally match well the paces of conodont δ 18 O (low‐to‐high) and Δ 13 Ccarb‐org (high‐to‐low ) fluctuations from the identical section published previously. These Sr isotopic fluctuations thus corroborate the cyclic variations in volcanic activity/flux and weathering intensity/riverine flux in parallel with climate warm‐to‐cool fluctuations. Mass balance modelling shows the first exceptionally high Sr isotope spike (I) could have been only yielded by a dramatic increase in terrestrial flux in a somewhat restricted Palaeo‐Tethys, likely due to the closure of the oceanic domain between Laurussia and Gondwana and sea‐level fall. This scenario would enhance the seawater eutrophication/anoxia in the pericontinental basins along the Palaeo‐Tethys, causing initial strikes on the low‐latitude shallow marine benthos. Subsequently, the frequent climatic fluctuations may have further caused escalating detrimental ecological pressures, leading to their massive demise.